2007
DOI: 10.1136/adc.2006.112136
|View full text |Cite
|
Sign up to set email alerts
|

Objective measurement of levels and patterns of physical activity

Abstract: Objective: To measure the levels and patterns of physical activity, using accelerometers, of 11-year-old children participating in the Avon Longitudinal Study of Parents and Children (ALSPAC). Design: Cross-sectional analysis. Setting: ALSPAC is a birth cohort study located in the former county of Avon, in the southwest of England. This study used data collected when the children were 11 years old. Participants: 5595 children (2662 boys, 2933 girls). The children are the offspring of women recruited to a birth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

58
408
18
22

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 448 publications
(506 citation statements)
references
References 36 publications
(41 reference statements)
58
408
18
22
Order By: Relevance
“…Other research suggests that greater physical activity engagement occurs school time (Fairclough et al, 2012;Ridgers, Timperio et al, 2011) because school provides specific physical activity opportunities within the school day (physical education, recess), contributing to overall physical activity (Stratton & Mullen, 2005). However, other research suggests that children are most active after school and that it is the differences in after school activity accounts for differences in overweight/obese vs. normal children and inactive vs. active children (Deforche et al, 2009;Riddoch, Mattocks et al, 2007;Olds, Maher & Ridley, 2011). Eyre et al (2013a) is the only study to consider within day patterns of PA in SA children.…”
Section: Environmental Differencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Other research suggests that greater physical activity engagement occurs school time (Fairclough et al, 2012;Ridgers, Timperio et al, 2011) because school provides specific physical activity opportunities within the school day (physical education, recess), contributing to overall physical activity (Stratton & Mullen, 2005). However, other research suggests that children are most active after school and that it is the differences in after school activity accounts for differences in overweight/obese vs. normal children and inactive vs. active children (Deforche et al, 2009;Riddoch, Mattocks et al, 2007;Olds, Maher & Ridley, 2011). Eyre et al (2013a) is the only study to consider within day patterns of PA in SA children.…”
Section: Environmental Differencesmentioning
confidence: 99%
“…Previous studies have found that children are more active on weekdays (Duncan, Schofield & Duncan, 2006;Duncan, Al-Nakeeb, Woodfield & Lyons 2007;McGall, McGuigan & Nottle, 2011;Oliver, Schofield & Kilt, 2007;Owens et al, 2009;Riddoch, Mattocks et al, 2007). Research suggests that highly active children spend more time in physical activity before school, during class, lunch and after school (Rowlands, Pilgrim & Eston, 2008).…”
Section: Environmental Differencesmentioning
confidence: 99%
“…This topic is pertinent for a number of reasons. First, there are concerns in respect to childhood inactivity (Riddoch, et al, 2007; see also Hillman, 2008 for contextual issues); if inactivity impairs cognition, this trend may lead to general declines in academic attainment. Second, with increased pressures on schools to achieve academic targets, the number of hours allocated to physical education have been reduced (Hardman, 2008); such reductions provide less opportunity for (acute) post-exercise enhancements of cognition.…”
Section: Introductionmentioning
confidence: 99%
“…More reliable and accurate measurements can be gained through the use of various monitoring devices. These include pedometers (step counters) and accelerometers, the latter of which can provide additional data on daily activity [6,7]. A result of improved accessibility and cost, the use of pedometers and accelerometers in clinical research has significantly increased over the past decade [8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%